Gender and Justice: the power to name - Veleanu, Corina (Comparative Legilinguistics, 2023)
We propose a trilingual jurilinguistic analysis on the place of the feminine in the world of justice, which will be based on examples identified in French, Spanish and English. A diachronic and contrastive perspective will be favored, through two questions which will question the way of naming inequality by the names of functions which are declined in the feminine, on the one hand, and the names of offenses against women, on the other hand. other side. We will explore the importance of the name and the action of naming the legal reality, considered under several aspects (psychological, political, linguistic, legal, social) of our social organization, while observing that the feminine is present in legal language in different ways, each language employing and imagining its own solutions.